Revealing Roz’s emotional growth through mood system analysis in The Wild Robot movie - Fitria, Dhea Rizky; Rusmana, Dadan; Yatmikasari, Ika (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This research explores Roz's emotional growth as reflected through her language choices in The Wild Robot movie using the Systemic functional Linguistics (SFL) framework, specifically the Mood system, as well as Barrett's Constructed Emotion theory. This study aims to analyze how Roz's transition from a task-focused robot to an emotionally aware being is reflected through Mood types: declarative, interrogative, and imperative. Using a qualitative descriptive method, Roz's utterances are analyzed based on Mood types and their interpersonal meanings. The results show that declaratives dominate at all stages of Roz's development, but change from mechanical and logical statements to reflective and relational expressions. Interrogatives decreased in frequency, but became more profound when used to explore abstract concepts such as love. Meanwhile, imperatives transform from procedural commands to expressions of protection and care. These linguistic changes reflect Roz's emotional development, which is supported by Barrett's theory that emotions are constructed through social, psychological, and neurological experiences. This research highlights the relationship between language and character development, and contributes to understanding how fictional dialog can convey emotional development.